Trabalho pedagógico multifacetado e a educação infantil na pandemia: uma análise dos movimentos de sentidos - De Toni, Dulcineia Libraga Papalia (2022)
This study is part of Kairós – Study and Research Group on Work, Education and Public Policies, linked to Research Line 2 – Public Educational Policies, Educational Practices and their Interfaces, of the Graduate Program in Education at the Federal University of Santa Maria. The research theme refers to the rights of learning and development in policies for Early Childhood Education, in particular, the right to play and the pedagogical work of teachers in the Municipal Network of Santa Maria. The research was problematized as follows: considering the context of a pandemic and the learning and development rights provided for in the policies for Early Childhood Education, how teachers of preschool children, from the Municipal Network schools in Santa Maria, elaborate, describe and visualize the senses in their pedagogical work, especially regarding the right to play? The initial assumption of the research was that, in order to produce a practical, transformative pedagogical work that has meaning and significance for teachers and children, it is important that teachers understand their work and play as a whole, in their theories. It was elaborated as a general objective: to analyze the meanings produced by preschool teachers about the pedagogical work they developed in the context of the pandemic, especially about playing, among the learning and development rights provided for in Early Childhood Education policies. The research has a dialectical approach, and had as reference the metaphor of the patchwork quilt, emphasizing that a ready-made quilt does not exhaust all the possible possibilities of analysis, after all, like the patchwork, the research could have been arranged in another way. Data production was based on questionnaires, interviews, pedagogical political projects (PPPs), the study of the Santa Maria Curriculum Guiding Document (DOC), the Gaucho Curriculum Reference for Early Childhood Education (RCGEI), the National Curriculum Guidelines for Early Childhood Education (DCNEI) and the National Curricular Common Base (BNCC), having as theoretical-methodological foundation, from a critical perspective, the Analysis of Movements of Senses (AMS). In the final considerations, the period of adversity is revisited and ennobles the actions of teachers in facing the adversities of the pandemic by Covid-19. The overcoming to deal with the unusual, the sense of collectivity and the multiple forms of work made the teachers develop a multifaceted pedagogical work. In the end, the initial assumption is resumed and possible answers to the questions proposed for the research are elaborated, presenting two considerations, one about the work that the teachers developed and the other about the right to play.